PELAKSANAAN PROGRAM DATA PROFIL DESA DAN KELURAHAN DALAM PENYELENGGARAAN PEMERINTAHAN DESA (DESA DAUH PURI KANGIN, KECAMATAN DENPASAR BARAT, KOTA DENPASAR) - Kharisma Winanda Putra, Putu Gede; Parwata, I Gusti Ngurah (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013, 2013)
One of the tasks of assistance given to the village government is the Profile Villageprogram. Its legal basis is the Ministerial Regulation No. 12 Year 2007 on Guidelines forthe Preparation and Utilization Data Profile of the Village. The issue is how the ProgramImplementation Profile village in Dauh Puri Kangin Village in West Denpasar of DenpasarDistrict and what factors that effecting the Program Implementation Profile village inDauh Puri Kangin Village in West Denpasar of Denpasar District. This research isempirical legal research with interview data collection techniques. The implications of theresearch indicated that the implementation of the profile village program in the Dauh PuriKangin Village in West Denpasar of Denpasar District has not been effectively, Becausethere is no training or technical training to the preparation and utilization profile data ofthe village, The factors which becomes an obstacle in the Profile Village programs in DauhPuri Kangin Village in West Denpasar of Denpasar District taken from lack ofunderstanding of the village employee who was given the task of data recording proceduresprofile village.
Keywords: Profile Village, Population Administration, Village Government